CD21lo/−CD27−IgM− Double-Negative B Cells Accumulate in the Joints of Patients With Antinuclear Antibody-Positive Juvenile Idiopathic Arthritis - Dirks, Johannes; Fischer, Jonas; Haase, Gabriele; Holl-Wieden, Annette; Hofmann, Christine; Girschick, Hermann; Morbach, Henner (Frontiers in Pediatrics, 2021)
Juvenile Idiopathic Arthritis (JIA) encompasses a heterogeneous group of diseases. The appearance of antinuclear antibodies (ANAs) in almost half of the patients suggests B cell dysregulation as a distinct pathomechanism in these patients. Additionally, ANAs were considered potential biomarkers encompassing a clinically homogenous subgroup of JIA patients. However, in ANA+ JIA patients, the site of dysregulated B cell activation as well as the B cell subsets involved in this process are still unknown. Hence, in this cross-sectional study, we aimed in an explorative approach at characterizing potential divergences in B cell differentiation in ANA+ JIA patients by assessing the distribution of peripheral blood (PB) and synovial fluid (SF) B cell subpopulation using flow cytometry. The frequency of transitional as well as switched-memory B cells was higher in PB of JIA patients than in healthy controls. There were no differences in the distribution of B cell subsets between ANA- and ANA+ patients in PB. However, the composition of SF B cells was different between ANA- and ANA+ patients with increased frequencies of CD21lo/- CD27-IgM- “double negative” (DN) B cells in the latter. DN B cells might be a characteristic subset expanding in the joints of ANA+ JIA patients and are potentially involved in the antinuclear immune response in these patients. The results of our explorative study might foster further research dissecting the pathogenesis of ANA+ JIA patients.